Algorithmic Dominance and The Deconstruction of Truth: Al-Ghazali’s Epistemological Critique of The Epistemic Authority of Artificial Intelligence - Mursyidul Haq Firmansyah; Fajrul Ilmi Darussalam; Arrasikhu Fililmi (Aqlania, 2026)
Artificial intelligence (AI) not only functions as a tool for computational work, but also plays the role of a socio-technical intermediary for epistemic authority. In this paper, the authors investigate how algorithmic systems are disrupting the standards through which we identify truth and explore al-Ghazali's views on Epistemology. Qualitative library research and conceptual-philosophical analysis have been the primary methods for this research. Among the major works studied were al-Munqidh min al-Dalal, Mishkat al-Anwar, and Kitab al-‘Ilm, besides confirmed scholarship on generative AI, algorithmic mediation, and al-Ghazali. "Deconstruction" denotes, to the greatest extent, the change in the standards or parameters for truth that are displaced or removed from that which corresponds and justifies, to that which is probable, fluent, widely visible, and performs well on the platform. The researchers point out that if Al-Ghazali's idea of certainty as well, the methodological doubt that goes hand in hand with an examination of reason, limits of human perception and reasoning, a divine source in man (illuminated understanding), as also ethical unity of knowledge and action is taken together, then one has a strong critical viewpoint against the algorithm which wants to lay down the absolute truth. The main contribution of this paper is the Ghazalias verification matrix, namely, source auditing, degrees of certainty, ethical reason, and ultimately, human moral responsibility. Therefore, AI is not just a machine but an assistance in cognition whose generated works should be considered only as potential statements that still need validation. It is not, as such, a being that autonomously possesses truth.